Cardiovascular risk assessment for primary prevention in Malawian HIV patients on ART: are measurements of glycated hemoglobin and lipids worth the effort? - Kumwenda, Tapiwa; Buleya, Shameem; Matanje, Beatrice; Heller, Tom; Phiri, Sam; Neuhann, Florian; Steffen, Hans-Michael (AIDS <London>, 2021)
An abstract is unavailable.